Designing amphiphilic branched polymers for supramolecular self-assembly. Issue 9 (18th August 2021) - Venu, Parvathy; Kumar, Rajan; Chethelen, Roshni J.; Shunmugam, Raja
Abstract: Recently, researchers are exploring the potential of polymer chemistry a lot in therapeutics. In conventional non-targeted polymeric drug delivery, an array of unwanted side effects was identified due to the release and distribution of therapeutic molecules into healthy cells. Consistent efforts are made to diminish such effects by encapsulating drug molecules into a well-developed stimuli-responsive nanocarrier that directly affects cells. Herein, we have designed to synthesize a nanocarrier, which was developed to carry any hydrophobic drug moiety through the bloodstream and finally target the infected area. For the greater assembly of molecules in the aqueous medium, we have incorporated self-assembly criteria into our design in the simplest way. Caprolactone (hydrophobic) and polyethylene glycol derivative (hydrophilic) were carefully chosen as the components to integrate amphiphilicity to the system to guarantee well organized self-assembled structures. Click chemistry (being stereospecific, simple to perform, broad in scope and most importantly high yielding) is a very productive method that is used in the synthetic procedure of connecting the new initiator molecule with the hydrophilic and hydrophobic part of the system. It is done just after the successful process of ring-opening polymerization. The critical micelle concentration of the self-assembled nanocarrier was found to be 235 μg/mL and the hydrodynamic radius measured using dynamic light scattering was noted as 24 nm. The micelles formed in aqueous solution were observed as spherical in shape under scanning electron microscope as well as transmission electron microscope. Graphical Abstract: UF0001